1999
DOI: 10.1159/000028839
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome after Selective Posterior Rhizotomy in Children with Spastic Cerebral Palsy

Abstract: A retrospective analysis of data collected prospectively was performed to determine the long-term outcome of lumbosacral selective posterior rhizotomy (SPR) in children with spastic cerebral palsy (CP). The study population comprised children with spastic CP, who had SPR more than 4 years prior to the time of the study and had quantitative standardized assessments of lower limb spasticity (Ashworth scale), range of motion measured goniometrically, muscle strength (MRC scale) and ambulatory function, both preop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 22 publications
(35 reference statements)
4
25
0
2
Order By: Relevance
“…Although MMT is not a consistent measure of strength in patients with neurological disorders, there have been studies where strength has been measured in MMT 1920. Subjects were allowed to lean back until tension in the hamstrings was relieved.…”
Section: Methodsmentioning
confidence: 99%
“…Although MMT is not a consistent measure of strength in patients with neurological disorders, there have been studies where strength has been measured in MMT 1920. Subjects were allowed to lean back until tension in the hamstrings was relieved.…”
Section: Methodsmentioning
confidence: 99%
“…However, the results in the body function and structure domain were not mentioned separately for the patients in the control group. Six further Level IV studies including 244 patients reported outcomes in the domain of body structure and body function 10,14,18,21,23,25 . A significant decrease in spasticity and range of motion was found was found 5 years after SDR in four studies 10,18,19,21 and in one study 20 years after SDR 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Six further Level IV studies including 244 patients reported outcomes in the domain of body structure and body function 10,14,18,21,23,25 . A significant decrease in spasticity and range of motion was found was found 5 years after SDR in four studies 10,18,19,21 and in one study 20 years after SDR 14 . One Level IV study reported a significant improvement of gait performance in a subgroup of children that have been younger than 5 years old when SDR was performed 23 .…”
Section: Discussionmentioning
confidence: 99%
“…This intragroup variability in the time between baseline and the most recent assessment was not considered to be a significant confounder, since it has been found previously that by 1 year after SDR, the patient’s condition has stabilized and an accurate assessment of the effect of the operation can be made [5, 21]. Another confounder was the fact that 6 children in group 1 and 3 in group 2 had intervening orthopedic procedures that may have affected the outcomes.…”
Section: Discussionmentioning
confidence: 99%